2020
DOI: 10.1155/2020/7805393
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hydroxysafflor Yellow A on Nephropathy by Attenuating Oxidative Stress and Inhibiting Apoptosis in Induced Type 2 Diabetes in Rat

Abstract: Diabetic nephropathy (DN) is a serious complication of diabetes mellitus, and its prevalence has been increasing all over the world, which is also the leading cause of end-stage renal failure. Hydroxysafflor yellow A (HSYA) is the main active chemical component of Carthamus tinctorius L., and it is commonly used in patients with cardiovascular and cerebrovascular diseases in China. The aim of this study was to investigate the renal protective effects and molecular mechanisms of HSYA on high-fat diet (HFD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…Traditional Chinese medicine (TCM) has already shown its effects in treating DN proteinuria and was able to provide a variety of effective renoprotective extracts [ 4 ]. In recent years, kaempferol (Ka) and hydroxysafflor yellow A (HSYA), two active components of safflower, attracted attention for their roles in ameliorating diabetes-induced fibrosis and renal damage [ 5 , 6 ]. Safflower yellow injection (SYI), which contains more than 90% HSYA, is recommended by TCM experts for clinical treatment of DN in China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has already shown its effects in treating DN proteinuria and was able to provide a variety of effective renoprotective extracts [ 4 ]. In recent years, kaempferol (Ka) and hydroxysafflor yellow A (HSYA), two active components of safflower, attracted attention for their roles in ameliorating diabetes-induced fibrosis and renal damage [ 5 , 6 ]. Safflower yellow injection (SYI), which contains more than 90% HSYA, is recommended by TCM experts for clinical treatment of DN in China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed to study the protective effect of BFO on NRK-52E cell apoptosis and oxidative stress induced by HG. Although the exact mechanism of HG-induced renal tubular epithelial cell injury has not yet been fully clarified, researches have shown that oxidative stress and apoptosis play important roles in the development and pathogenesis of DN ( Tiong et al, 2019 ; Lee et al, 2020 ). NRK-52E cells cultured with HG are widely used as a DN model ( Hou et al, 2014 ; Slyne et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these data suggest a direction for exploring the individual components of BSHX decoction. As a main chemical component of Carthami Flos , Hydroxysafflor yellow A has been demonstrated to be able to reduce high glucose-induced pancreatic β-cells apoptosis via PI3K/AKT and JNK/c-Jun signaling pathways ( Zhao et al, 2018 ; Lee et al, 2020a ), and exerts a renal protective effect by inhibiting oxidative stress, reducing inflammatory responses, and attenuating renal cell apoptosis in rats with a HFD- and STZ-induced diabetes ( Lee et al, 2020b ). Loganin, a major chemical component of Corni Fructus , had the highest concentration in the medicated serum in this study, and exerts an early renal protective role in DN by inhibiting connective tissue growth factor ( Jiang et al, 2012 ), and alleviating the loss of podocytes induced by high glucose via targeting AGEs-RAGE and its downstream pathways, p38MAPK and Nox4, in vivo or in vitro ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%